A1.27 MPGES-1 deletion increases prostacyclin and evades the elevated systemic ADMA associated with COX-2 inhibitors: relevance to cardiovascular safety of mpges-1 inhibitors. (24th February 2016) - Raouf, J; Kirkby, NS; Ahmetaj-Shala, B; Liu, B; Mazi, SI; Korotkova, M; Zhou, Y; Mitchell, JA; Jakobsson, PJ
Abstract : Background and objective: Cyclooxygenase-2 (COX-2) is involved in the generation of prostanoids such as prostaglandin (PG)E2, prostacyclin (PGI2 ) and thromboxane (TXA2 ); PGE2 is involved in inflammation/pain, whereas the second two are involved in cardiovascular homeostasis. Nonsteroidal anti-inflammatory drugs (NSAIDs) inhibit COX-2 and are used to treat inflammation, however they cause cardiovascular side effects. The mechanisms for this include reduced vascular and/or renal PGI2 and, by effects on the renal medulla, increased dimethylarginine (ADMA), an endogenous inhibitor of endothelial nitric oxide synthase (eNOS). Microsomal PGE2 synthase 1 (mPGES-1) has been intensively investigated as a safer, alternative anti-inflammatory drug-target. We aimed to investigate how mPGES-1 versus COX-2 influences pathways associated with PGI2, ADMAand eNOS in order to assess the potential cardiovascular safety of mPGES-1 as a drug-target. Materials and Methods: Experiments were performed on mPGES-1 +/+ (WT) and mPGES-1 -/- (KO) mice as well as PGI2 synthase (PGIS -/- ) KO mice. In some experiments WT mice were treated orally with the selective COX-2 inhibitor, parecoxib (100mg/kg; 5 days). Plasma was analysed by immunoassay for ADMA and PGI2, or by biochemical assay for creatinine. Renal medulla was stimulated with Ca 2+ ionophore and PGE2 release measured by immunoassay. Gene expression levels were determined using TaqMan assays. Vascular function (eNOS response) was assessed in isolated aorta stimulated with acetylcholine by wire myography. Results: WT mice treated with parecoxib displayed no change in plasma PGI2 levels but, in contrast, mPGES-1 KO mice had significantly higher plasma levels of PGI2 . In the kidney, mPGES-1 gene expression was lower in the renal medullathan the cortex, and in agreement; mPGES-1 deletion did not alter renal medulla PGE2 production. mPGES-1deletion had no effect on genes responsible for the production/breakdown of ADMA in the kidney (PRMT1, AGXT2, DDAH1/2). Plasma creatinine/ADMA was elevated in mice treated with parecoxib or PGIS KO mice but unaffected in mPGES-1 KO mice. Furthermore, mPGES-1 deletion significantly improved the eNOS-driven dilator response to acetylcholine in aorta. Conclusions: Targeting mPGES-1 KO avoids the effects of COX-2 inhibition on renal PGI2 /ADMA pathway and therefore spares vascular eNOS responses. This supports the development of selective inhibitors of mPGES-1 to more safely treat inflammation.